Mengenal Para Mufassir pada Generasi Tabi’in Beserta Contoh Ayat Al-Quran Berdasarkan Corak Penafsiranya - Aswati Sarah; Ummiyah, Meity; Gunawan, Akmal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tafsir is the science of understanding the verses of the Al-Quran which functions as mubayyin (explanation) of the meaning and significance of the contents of the verses of the Al-Quran so that the meaning can be understood and comprehended by all groups and becomes a guide or guidance in life for Muslims. The development of Al-Quran interpretation began during the time of Rassulullah SAW and continued to develop from the time of the companions, tabi'in to the modern era. This research discusses the biographies of tabi'in and also includes several examples of interpretations of Al-Quran verses based on these interpretations. This research aims to get to know the mufasssir during the tabi'in period and find out traces of their biographies and find out examples of interpretations of Al-Quran verses based on interpretive styles. This research method uses qualitative methods and literature studies and examines tafsir books, hadith books, Islamic book references, language book references and portal media such as journals. The results of this research serve as a guide for Muslims to learn more about tabi'in biographies and upgrade the interpretation of verses by including examples of interpretations of verses based on their style.